Cross-dressing and Modern Nepali Plays: A Contextual Reading - Rijal, Shiva; Dahal, Arvind; Bogati, Sumitra (The Spectrum, 2026)
This paper explores the presence of cross-dressing based theatrics in Mukunda Indira, Sahanshila Sushila and Masan written by the first generation modern male Nepali playwrights Balkrishna Sama (1902-1981), Bhimnidhi Tiwari (1911-1973) and Gopal Prasad Rimal (1918-1973) respectively. It does so by defining the cross-dressing as dominant theatrics in the Kathmandu Valley during the first half of twentieth century. There did exist a number of theatre groups active during the Gaijatra festival that falls in August, and artists known for their cross-dressing talents were popular. The Rana rulers employed artists in their palaces and would invite theatre talents from the then Calcutta to train their subjects. By contextualizing these plays and playwrights to the aesthetic and social forces of the 1930s and 1940s, this paper reads selected dramatic scenes the plays as sites to excavate and examine presence of cross-dressing-based theatrics of the time. Drawing insights from Stephen Greenblatt and others’ research on cross-dressing based theatre of renaissance London, the paper interprets the three plays and reaches to a conclusion that cross-dressing based aesthetics needs to be discussed and defined as dynamic artistic force behind the making of modern Nepali theatre.